Effects of Low Concentration of Glyphosate-Based Herbicide on Genotoxic, Oxidative, Inflammatory, and Behavioral Meters in Danio rerio (Teleostei and Cyprinidae) - Eduardo Bortolon Ribas; Gustavo Colombo Dal-Pont; Ariana Centa; Marcos Otávio Bueno; Ricardo Cervini; Rosana Claudio Silva Ogoshi; Claudriana Locatelli (Biochemistry Research International)
The glyphosate herbicide is a pesticide widely used in the world and can contaminate soil, air, and water. The objective of this work was to evaluate the toxicity of a glyphosate-based herbicide (GBH) in zebrafish (Danio rerio). Fish were exposed to different concentrations of GBH (0, 50, 250, and 500 µg/L) for 96 hours. Brain, liver, and blood were collected for biochemical and genotoxicity analyses, and behavioral tests were performed. The results showed that there was a reduction in the activity of the antioxidant enzymes of catalase (CAT) and glutathione-S-transferase (GST) in the liver at all concentrations and at the highest concentration in the brain. There was also a reduction in lipid peroxidation in the liver at all concentrations of glyphosate. There was an increase in micronuclei in the blood at the 500 µg/L concentration. However, the count of nuclear abnormalities showed no differences from the control. Interleukin-1beta (IL-1β) generation was inhibited at all concentrations in the liver and at the highest concentration in the brain. No significant differences were found in the behavioral test compared to the control. The results showed that acute exposure to GBH promoted an inflammatory event, which reduced the efficiency of antioxidants, thus producing a disturbance in tissues, mainly in the liver, causing immunosuppression and generating genotoxicity.